Clemastine Alleviates Depressive-Like Behavior Through Reversing the Imbalance of Microglia-Related Pro-inflammatory State in Mouse Hippocampus - Su, Wen-Jun; Zhang, Ting; Jiang, Chun-Lei; Wang, Wei (Frontiers in Cellular Neuroscience, 2018)
Abstract: Backgrounds Abundant reports indicate that neuroinflammatory signaling contributes to behavioral complications associated with depression and may be related to treatment response. The glial cells, especially microglia and astrocytes in brain regions of hippocampus and medial prefrontal cortex, are major components of CNS innate immunity. Moreover, purinergic receptor P2X, ligand-gated ion channel 7 (P2X7R) was recently reckoned as a pivotal regulator in central immune system. Besides, it was pointed out that clemastine, a first-generation histamine receptor H1 (HRH1) antagonist with considerable safety profile and pharmacological effect, may suppress immune activation through modulating P2X7R. Herein, we investigated the potential anti-neuroinflammatory effects of clemastine on CUMS-induced depressive-like behavior in a mouse model. Methods Male BALB/c mice were subjected to chronic unpredictable mild stress (CUMS) for 4 weeks, some of them were injected with clemastine fumarate solution. After the stress procedure, behavioral tests including sucrose preference tests, tail suspension tests and locomotor activities were performed to evaluate depressive-like phenotype. Subsequently, expression of cytokines and microglia-related inflammatory biomarkers were assessed. Results In the present research, we found that clemastine significantly reversed both the declination of SPT percentage and the extension of TST immobility durations in depression mouse model without affecting locomotor activity. Also, we observed that clemastine regulated the imbalance of pro-inflammatory cytokines including IL-1β and TNF-α in the hippocampus and serum of depressive-like mice. Additionally, clemastine significantly suppressed microglial M1-like activation specifically in the hippocampus, and also improved hippocampal astrocytic loss. Furthermore, clemastine downregulated hippocampal P2X7R without interfering with the expression of HRH1. Conclusion As a safe and efficient anti-allergic agent, clemastine could impressively alleviate stress-related depressive-like phenotype in mice. Further evidence supported that it was because of the potential function of clemastine in modulating the expression of P2X7 receptor possibly independent of HRH1, therefore suppressing the microglial M1-like activation and pro-inflammatory cytokines release in brain regions of hippocampus rather than mPFC.